Loneliness in the Middle of Connection: Adolescent Existentialism in a Digital Context - Otto Mart Andreas; Bukidz, Danny Philipe; Samosir, Elisabet Marthawati (PT FORMOSA CENDEKIA GLOBAL, 2025)
In the 21st century, advancements in digital technology have reshaped social structures and behaviors, particularly among adolescents navigating identity formation. This study explores the phenomenon of digital loneliness in adolescents through the lens of existentialism, a philosophy centered on life’s meaning and individual freedom in social contexts. While digital communication offers convenience, many adolescents experience alienation due to superficial and shallow interactions. Although technology enables the creation of virtual identities, it often limits the authenticity of interpersonal relationships. This research reveals that reliance on social media can lead to feelings of loneliness and inauthenticity. However, with awareness of individual responsibility and mindful use of technology, adolescents can foster meaningful relationships and discover purpose in their digital existence, making existentialism both relevant and practical.